Метод теоретичного опису критичної поведінки 3D-моделі фазового переходу в зовнішньому полі - Козловський, М. (Праці наукового товариства ім. Шевченка, 2011)
he paper is devoted to the presentation of the analytic method describing the critical behavior of the 3D Ising model in the external field It is a continuation of the phase transition theory proposed by I. .R Yukhnovkii which uses the Collective Variables method. The generalization concerns the investigation of the external field effect on the behaviour of such characteristics as order parameter, susceptibility, heat capacity, etc. Within the framework of a simple model, the evaluation of critical exponents as well as critical amplitudes for different physical quantities is carried out. The general scaling form for free energy near the phase transition point is suggested. The crossover equation of state is obtained It represents the explicit dependence of the order parameter on the reduced temperature and external field.